Studi Literatur Potensi Antivirus Laktoferin Susu Kuda Terhadap Virus Japenese Encephalitis - Awa, Diana Rambu Naha Ana; Detha, Annytha I.R; Saputra, Agus (Jurnal Veteriner Nusantara, 2024)
Lactoferrin is a type of protein found in many fluid secretions such as saliva, tears, blood, neutrophil and milk. Subcutaneus or oral administration of lactoferrin can inhibit the growth of tumor implants and have a preventive effect on metastases. According to lactoferrin, viruses carried by mosquitoes, such as the Japanese encephalitis, can be inhibited. This virus causes Japanese encephalitis which is zoonotic and transmitted by the bite of the Culex tritaeniorhynchus as the main vector. Therefore, it is interesting to conduct an in-depth study related to the lactoferrin antiviral potential on Japanese encephalitis virus. The aim of this literature study is to identify the mechanism of the lactoferrin antiviral ability of horse milk and analyze the lactoferrin potential of horse milk on Japanese encephalitis virus. In addition, it was obtained from searches and collections of various sources of reference using Mendeley and Google Scholar applications with a total of 52 references. After being analyzed and assessed, the mechanism of antiviral ability lactoferrin mediated by the N-lactoferrin lobe and various antiviral mechanisms, such as attachment of the virus to the host cell membrane and adsorption of the virus to the host cell.